Diagnosis Of Root Canal Obturation Failure (Tooth 24) Due To Post-Endodontic Treatment Flare-Up With Cone Beam Computed Tomography (CBCT) Radiography - tyana alma shamira; Indra Gunawan; Fiqi Faisal Kirom (International Journal of Health Engineering and Technology, 2026)
Post-obduration flare-up is a rare acute complication characterized by severe pain occurring within a few days following endodontic treatment. In a treated tooth, acute pain triggered by masticatory forces often leads to the initial clinical suspicion of a Vertical Root Fracture (VRF). This case report aims to demonstrate the crucial role of CBCT in diagnosing the etiology of flare-up in tooth 24. An 18-year-old male patient experienced severe pain on tooth 24, 1-3 days post-obduration, exacerbated after consuming satay. Initial periapical radiography (2D) failed to show a VRF or clear periapical lesions. Subsequent CBCT examination (3D) ruled out VRF and instead revealed a non-hermetic root canal filling defect (intraradicular void) in the mid-root section. CBCT proved essential for the definitive diagnosis, guiding the treatment plan toward retreatment and providing a better prognosis compared to VRF.